THE ROLE AND IMPORTANCE OF INTERACTIVE METHODS IN IMPROVING STUDENTS’ SPIRITUAL AND MORAL EDUCATION - Xatamova Ma’rifat Yorkinovna (NEW APPROACHES IN EDUCATION: PEDAGOGY, INNOVATION, AND DEVELOPMENT, 2026)
Abstract: This article explores the role and significance of interactive teaching methods in improving students’ spiritual and moral education. In modern educational practice, the shift toward learner-centered approaches has emphasized the importance of active participation, critical thinking, and collaborative learning. The study applies a mixed-methods approach to analyze how interactive methods influence students’ moral development, engagement, and learning outcomes. The findings indicate that the use of interactive strategies significantly enhances students’ interest, promotes deeper understanding of ethical values, and supports the development of independent thinking. The article concludes that interactive methods are essential tools in strengthening the effectiveness of spiritual and moral education.